KEBERHASILAN TUMBUH TANAMAN GAHARU (Aquilaria malaccensis) ASAL PROVENANSI AMBON DAN LAIMU DI DESA HATUSUA, KECAMATAN KAIRATU, SERAM BAGIAN BARAT - Wattimena, Lenny Stien; Matinahoru, Johan; Tetelay, Febian (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Provenance testing is one of the tree breeding approaches to obtain quality seeds, a testing process is needed to find better seed sources in the development area. In this case the species chosen is Agarwood (Aquilaria malaccensis). The aim of this research is to understand the differences in growth of two provenances of gaharu plants (Aquilaria malaccensis) from Ambon Island Village and Laimu Village, Seram Island. This research took place in December 2022 and was carried out in the 2 year old Agarwood Plant Genetic Resources Area (Aquilaria malaccensis), in Hatusua Village, Kairatu District, West Seram Regency. Research shows that of 400 agarwood plants originating from Passo Village, only 309 survived and 91 died, so the percentage of surviving plants reached 77%. Meanwhile, for Laimu Village, of the same 400 plants, there are 315 that are still alive and 85 that are dead, so the percentage of living plants in Laimu Village is 79%. Based on this analysis, the calculated t-value is 2.16, while the t-table at α = 0.05 with 39 degrees of freedom is 2.02. This shows that the t-count is greater than the t-table, which indicates there is a significant difference between the provenances of Passo Village and Laimu Village. For plant diameter, the t-count was recorded at -0.21, and when compared with the t-table at α = 0.05 and 39 degrees of freedom which is 2.02, the t-count is smaller than the t-table. Therefore, there is no difference in diameter between the two provenances.